# Solve for y 5/3+3y=6y-2/15

53+3y=6y-215
Move all terms containing y to the left side of the equation.
Subtract 6y from both sides of the equation.
53+3y-6y=-215
Subtract 6y from 3y.
53-3y=-215
53-3y=-215
Move all terms not containing y to the right side of the equation.
Subtract 53 from both sides of the equation.
-3y=-215-53
To write -53 as a fraction with a common denominator, multiply by 55.
-3y=-215-53⋅55
Write each expression with a common denominator of 15, by multiplying each by an appropriate factor of 1.
Multiply 53 and 55.
-3y=-215-5⋅53⋅5
Multiply 3 by 5.
-3y=-215-5⋅515
-3y=-215-5⋅515
Combine the numerators over the common denominator.
-3y=-2-5⋅515
Simplify the numerator.
Multiply -5 by 5.
-3y=-2-2515
Subtract 25 from -2.
-3y=-2715
-3y=-2715
Cancel the common factor of -27 and 15.
Factor 3 out of -27.
-3y=3(-9)15
Cancel the common factors.
Factor 3 out of 15.
-3y=3⋅-93⋅5
Cancel the common factor.
-3y=3⋅-93⋅5
Rewrite the expression.
-3y=-95
-3y=-95
-3y=-95
Move the negative in front of the fraction.
-3y=-95
-3y=-95
Divide each term by -3 and simplify.
Divide each term in -3y=-95 by -3.
-3y-3=-95⋅(-13)
Cancel the common factor of -3.
Cancel the common factor.
-3y-3=-95⋅(-13)
Divide y by 1.
y=-95⋅(-13)
y=-95⋅(-13)
Simplify -95⋅(-13).
Cancel the common factor of 3.
Move the leading negative in -95 into the numerator.
y=-95⋅(-13)
Move the leading negative in -13 into the numerator.
y=-95⋅-13
Factor 3 out of -9.
y=3(-3)5⋅-13
Cancel the common factor.
y=3⋅-35⋅-13
Rewrite the expression.
y=-35⋅-1
y=-35⋅-1
Combine -35 and -1.
y=-3⋅-15
Multiply -3 by -1.
y=35
y=35
y=35
The result can be shown in multiple forms.
Exact Form:
y=35
Decimal Form:
y=0.6
Solve for y 5/3+3y=6y-2/15

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top